Gentoo penguin Spectramax transmission.xlsx - Peter Hadden; Misha Vorobyev; William Hadden; Charles McGhee; Jie Zhang (2023)
These are the raw data obtained using a SpectraMax 13x (Molecular Devices Inc, San Jose, CA) to determine the amount of light at each given wavelength transmitted through various ocular structures (cornea, lens, vitreous and nictitating membrane) and through the whole eye of the gentoo penguin Pygoscelis papua . There is both the raw transmission data (and, for G2, absorbance data, from which transmission is calculated) and the amount transmitted compared with the amount transmitted at 700 nm, expressed as a decimel where the transmission at 700 nm is 1.